TECNOLOGIAS DE APLICAÇÃO DE PRODUTOS FITOSSANITÁRIOS NO CONTROLE DE PERCEVEJOS PRAGAS NA CULTURA DA SOJA - Prado, E.p. [UNESP]; Raetano, C.g.; Christovam, R.s. [UNESP]; Aguiar-júnior, H.o.; Dal Pogetto, M.h.f.a. (Instituto Biológico, 2020)
Stink bugs are an important pest in the soybean crop. The aim of this research was to evaluate the control of this pest with pesticides applied at two air speeds using an air assisted sleeve boom sprayer arranged with two nozzles. Two experiments were carried out at FCA/UNESP Botucatu, SP (Brazil), using soybean plants of the Conquista variety (season 2006/2007). The experimental design was randomized blocks with 5 treatments and 4 repetitions in a 2 x 2 + 1 factorial scheme (two levels of air speed, 0 and 100%, two nozzles: flat fan nozzle AXI 11002 and hollow cone nozzle JA-2, plus nontreated plots). The insecticide tiametoxam associated with lambdacialotrina (experiment 1) at 25.38 + 19.08 g i.a. ha-1 and endosulfan (experiment 2) at 437.5 g.i.a. per hectare were applied in the growth stage V6 with support of the spray Advanced Vortex 2000 using a volume rates of 200 L ha-1 for both treatments and experiments. The evaluations before (0) and 1, 3, 6, 10 and 14 days after applications were made by the method of hits on the cloth. The average numbers of stink bugs were significantly lower in treated plots in relation to nontreated plots. In general, there was no statistical difference between the application technologies in both experiments.

Os percevejos fitófagos são importantes insetos-pragas na cultura da soja, causando danos desde a formação das vagens até o final do desenvolvimento dos grãos. O trabalho objetivou avaliar o controle desses insetos-pragas (complexo de percevejos) após o tratamento com inseticidas sob duas velocidades da assistência de ar junto à barra de pulverização combinadas a duas pontas de pulverização. Dois experimentos foram conduzidos na Faculdade de Ciências Agronômicas/UNESP – Campus de Botucatu, safra 2006/2007 na cultura da soja, var. Conquista, no delineamento experimental em blocos ao acaso, com esquema fatorial 2 x 2 + 1 (dois níveis de ar, 0 e 100%; duas pontas de pulverização, JA-2 e AXI 11002, mais testemunha). No estádio de desenvolvimento R6 foi realizada uma pulverização com os inseticidas tiametoxam associado com lambda-cialotrina (experimento 1) na dosagem de 25,38 + 19,08 g i.a. ha-1 e endosulfan (experimento 2) na dosagem de 437,5 g.i.a. ha-1. A aplicação foi feita com um pulverizador Advanced Vortex 2000 conferindo um volume de calda de 200 L ha-1. As avaliações antes (prévia) e com 1, 3, 6, 10 e 14 dias após a aplicação foram realizadas pelo método do pano-de-batidas. O número médio de percevejos foi significativamente menor nas parcelas tratadas em relação àquelas não tratadas. De modo geral, não houve diferença estatística entre as tecnologias de aplicação em ambos os experimentos.
EFFECT OF PESTICIDE APPLICATION TECHNOLOGIES IN THE CONTROL OF STINK BUGS IN THE SOYBEAN CROP
Keywords: Chemical control; pentatomidae pests; application technique; Controle químico; pentatomidae; pragas da soja; técnicas de aplicação